The Constitution of the City : Economy, Society, and Urbanization in the Capitalist Era - Scott, Allen J. (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book presents an exploratory account of the origins and dynamics of cities. The author recounts how the essential foundations of the urbanization process reside in two interrelated forces. These are the tendency for many different kinds of human activity to gather together to form functional complexes on the landscape, and the multifaceted intra-urban space-sorting crosscurrents set in motion by this primary urge. From these basic points of departure, the city in all its fullness emerges as a reflexive moment in social and economic development. The argument of the book is pursued both in theoretical and in empirical terms, devoting attention to the changing character of urbanization in the capitalist era. A point of particular emphasis concerns the peculiar patterns of resurgent urbanization that are making their historical and geographical appearance in the currently emerging phase of cognitive-cultural capitalism and that are now rapidly diffusing across the globe.